Rư̄ang Čhaophrayā Mahāsēnā (Bunnāk) - Kōmārakunmontrī (Chư̄n), Phrayā, 1891-1961; ʻAmō̜nsakprasit (ʻAt), Lūang, died 1950; Chœ̄i Bunnāk, died 1950 ([Krung Thēp] : Lūang Wičhitpramūankān, 1950)
Biography of Mahāsēnā (Bunnāk), Čhaophrayā, 1773-1805, former high government official during reign of King Rama I, includes genealogy of Bunnak family; cremation volume for Luang Amonsakprasit (At) and Nang Amonsakprasit (Choei).
Cover title.
Keywords: Bunnag family; Chœ̄i Bunnāk, -- died 1950 -- Death and burial; Mahāsēnā -- Čhaophrayā, -- 1737-1805.; Nobility -- Thailand -- Biography; Thailand -- History -- To 1782.; Thailand -- Genealogy